2019
DOI: 10.21608/jfds.2019.53498
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Okra Seeds Powder to Employ in some Foodstuffs Based on its Physical, Chemical and Sensorial Evaluation

Abstract: In the current paper, okra of Egyptian variety (Abelmoschus esculentus L.) seeds dry were used to assess physical characteristic, chemical analysis and applying of the seed for fortifying foods. Analysis including pH value, bulk density (g/ cm 3 ), crude protein (%), crude fiber (%), total phenolic (mg GAE/100g) and antioxidant activity (%)were 6. 43, 0.56, 23.95, 24.81, 34.29, 50.43, respectively. Moreover, considerable mineral contents. Also, the great of essential amino acids (EAA) were leucine (6.71%) foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…Regarding the TPC in okra seeds, various studies revealed significant differences in TPC values, which ranged from 278.3 to 13000 mg GAE kg −1 d.w. [10,59,71,72]. These results are significantly lower in comparison with the TPC of okra seeds found in our experiment.…”
Section: Total Polyphenol Contentcontrasting
confidence: 91%
“…Regarding the TPC in okra seeds, various studies revealed significant differences in TPC values, which ranged from 278.3 to 13000 mg GAE kg −1 d.w. [10,59,71,72]. These results are significantly lower in comparison with the TPC of okra seeds found in our experiment.…”
Section: Total Polyphenol Contentcontrasting
confidence: 91%
“…Thus, it maintained the balance of amino acids, which are essential for building proteins for hormones and enzymes, as well as increasing the synthesis of muscle proteins [25,26]. Okra seeds and fruits also contain high-quality proteins and a balance of essential amino acids [27]. Uric acid is the main product of the degradation of nitrogenous protein other than protein and purines in birds [28] and 80% of the total nitrogen is in the form of uric acid and 1-10% as urea [29].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hands, okra seed protein with good PER and net protein utilization (NPU) values is comparable to many cereals (excepting wheat) and its oil yield is similar to the most oil seed crops except oil palm and soybean oil (Kumar, et al, 2010). Also, a recent study confirmed that the great of essential amino acids of okra seeds powder were leucine (6.71%) followed by lysine (5.22%) (Abouel-Yazeed, 2019).…”
Section: Introductionmentioning
confidence: 82%
“…On the other hand, the information presented by Gemede et al (2015) showed that the potential nutritional importance of okra and its role in improved nourishment and health. In addition, it can use it to apply in manufacturing for dietary improvement, due to its several health benefits (Abouel-Yazeed, 2019).…”
Section: Carcass Characteristics and Internal Organsmentioning
confidence: 99%